Barriers and Biases in Computer-Mediated Knowledge Communication
XII, 334 p.
Keywords: This books deals with computer-mediated cooperation and communication scenarios in teaching and learning situations, leisure activities (e.g. laypersons looking for expert information on the internet), and net-based communication at work. Such scenarios will become increasingly important. But the successful use of such computer-mediated settings is not trivial. Cooperative learning and work itself requires special skills and strategies. And the technical settings with sometimes restricted, sometimes new possibilities for communication add problems on top of the cooperation itself. What are the barriers in computer-mediated communication for cooperative learning and work? Which are the most relevant biases in computer-mediated information processing? Based on empirical research the contributors from psychology, education and computer sciences offer different perspectives on the nature and causes of such barriers. The chapters also give an answer to the question how it might be possible to overcome these barriers and biases to fully gain advantage from the new technical opportunities. These results and answers are of interest for students as well as for researchers in all fields related to the use and evaluation of computer software in communication settings.